Yahweh's coming of age - Bembry, Jason,
In the Judeo-Christian tradition, the deity YHWH is often portrayed as an old man. One of the epithets used of YHWH in the Hebrew Bible, the Ancient of Days, is a source for this depiction of God as elderly. Yet, when we look closely at the early traditions of biblical Israel, we see a different picture : God is relatively youthful, a warrior who defends his people. This book is an examination of the question: How did God become old? The transformation from young deity to Ancient of Days took place at the intersection of two trajectories in the traditions of Israel. One trajectory is reflected in the way that apocalyptic traditions found in the book of Daniel recast the old Canaanite mythic imagery seen in the Ugaritic and early biblical texts. This trajectory allows YHWH to take on qualities, such as old age, that were not associated with him during most of Israel's history but were associated with El in the Canaanite traditions. The second trajectory, a depiction of Israel's God as elderly, is connected with the development of the idea of YHWH as father. The more comfortable the biblical tradents became with portraying YHWH as a father a metaphor that was not embraced in the early traditions the easier it became for the people of Israel to think of YHWH as occupying a stage of the human life cycle.